Albania : Staff Report for the 2004 Article IV Consultation, Fifth Review Under the Poverty Reduction and Growth Facility, Request for Extension of the Arrangement, and Financing Assurances Review. (IMF Staff Country Reports; Country Report, 2005)
This paper reviews Albania's 2004 Article IV Consultation, Fifth Review Under the Poverty Reduction and Growth Facility (PRGF), Request for Extension of the Arrangement, and Financing Assurances Review. The macroeconomic performance of the Albanian economy has been remarkable by both regional and international standards. After a slowdown in 2002, economic growth recovered to about 6 percent in 2003-04; and inflation declined, generally remaining within the 2-4 percent target range of the Bank of Albania. Some structural reforms also gained momentum in 2004-notably privatization and sectoral restructuring.